2005
DOI: 10.1002/arch.20048
|View full text |Cite
|
Sign up to set email alerts
|

Action of 24-epibrassinolide on a cell line of the beet armyworm,Spodoptera exigua

Abstract: The Spodoptera exigua cell line Se4 is sensitive for ecdysteroid activity stimulated by the insect molting hormone, 20-hydroxyecdysone (20E), showing a cease in cell proliferation (with 50% inhibition around 1 microM) and characteristic cell morphology changes with aggregation and formation of long filamentous cytoplasmic extensions. The bisacylhydrazine tebufenozide also triggered such typical cellular effects in Se4, and in addition, it showed an affinity for binding in competition with 3H-ponasterone A (PoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The first experiments showed that steroidal phytohormones could affect normal growth and development of insects. A number of BS effects were revealed at different levels [22], including intact animals [15,23,24], isolated tissues [23,25,26], cultured cells [27,28], particular insect neurons [29], and protein molecules (ecdysteroid receptors) [23,28,30,31]. However, the results of these experiments are not always consistent with each other.…”
Section: Effects On Insectsmentioning
confidence: 73%
See 1 more Smart Citation
“…The first experiments showed that steroidal phytohormones could affect normal growth and development of insects. A number of BS effects were revealed at different levels [22], including intact animals [15,23,24], isolated tissues [23,25,26], cultured cells [27,28], particular insect neurons [29], and protein molecules (ecdysteroid receptors) [23,28,30,31]. However, the results of these experiments are not always consistent with each other.…”
Section: Effects On Insectsmentioning
confidence: 73%
“…However, the affinity in most experiments was 10-to 1000 fold lower than that observed for binding to radiolabeled ponasterone A, and no competition at all was observed for EcR in intact Se4 cells even at relatively high (100 lM) concentration of EBl [28]. A number of synthetic hybrids of BS and ecdysteroids were prepared and assessed for their activities in the Drosophila melanogaster B II cell bioassay [33].…”
Section: Effects On Insectsmentioning
confidence: 98%
“…After incubation, the cell numbers were counted using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) (SigmaeAldrich) as a substrate according to Decombel et al (2005). The MTT assay is based on the enzymatic conversion of a yellow tetrazolium salt to an insoluble formazan product by the mitochondria of viable cells.…”
Section: Cytotoxic Effect Of Ssa In Insect Midgut Cf-203 Cellsmentioning
confidence: 99%
“…The Se4 cell line is sensitive for ecdysteroid activity stimulated by 20E and tebufenozide (Decombel et al, 2005) and can be used as a model to study the mode of action of ecdysteroids and their agonists. First, we investigated the relative potency of the four ecdysteroid agonists on cell proliferation in comparison with 20E.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, the cell numbers were counted with the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) technique according to Decombel et al (2005). Briefly, 100 µl of cell solution was transferred to a microtube (Eppendorf) and 100 µl of 1 mg/ml MTT solution was added.…”
Section: Comparative Potency Of Ecdysteroid Agonistsmentioning
confidence: 99%